Does Content Marketing on TikTok Impacts Female Gen Z’s Engagement? - Dharomesz, Vonezyo Yupanzara (Ecobuss, 2024)
This research examines the interactions between ads and young female TikTok users. Like social media platforms, content marketing has become very popular, encompassing the creation and dissemination of valuable, relevant, and consistent information over time. This revolutionary approach by TikTok to marketing allows marketers to interact with younger audiences via interactive content marketing. Specifically, this study uses a quantitative methodological framework in surveying 256 Generation Z females on TikTok about their content marketing consumption patterns and engagement. The research employs SEM using SmartPLS to explore the relationships between content marketing and customer engagement. The study findings are expected to demonstrate how well-focused content strategies can foster stronger ties leading to higher rates of brand involvement among female Generation Z TikTok users. According to this prediction, TikTok's content marketing significantly positively affects consumer engagement for female Gen Z users.